Paramètres cognitifs et psycholinguistiques des tâches en enseignement-apprentissage d’une langue étrangère - Pascale Goutéraux (Recherches en didactique des langues et des cultures)
The Common European Framework of Reference (CEFR) task-based approach highlights the part played by communicative tasks and real-life projects for the acquisition of a foreign language. And yet, applying the pedagogical principle that a learner’s communicative competence in a foreign language is best built through practising communication has proved insufficient in classroom situations. Communication in English classes involves a mix of authentic and simulated tasks conducive to the production of interrelated semantic, cultural, metacognitive and metalinguistic discourses, with a strong didactic potential for the development of oral proficiency. Taking into account such cognitive and psycholinguistic parameters as fluency, accuracy and semantic or linguistic complexity is another prerequisite to designing efficient communicative tasks. Although the Common European Framework does not deal with this problem, current international research in psycholinguistics and Second Language Acquisition explores both the ways to integrate these parameters in designing communicative tasks as well as the influence of scaffolding on the internalisation of a discourse competence. The convergence is striking between English-language research publications concerning the impact of Focus-on-Form methodology and French ‘enunciative’ studies analysing the contribution of consciousness-raising activities and metalinguistic branching out in communicative situations. This reflection is illustrated by the initial results of a longitudinal study on the evolution of French tenth graders’ oral proficiency in English.